Performance measuring for Chinese banks: cost efficiency and profitability - Xu, Meng (2017)
Chinese banking sector has finished three rounds of reforms while latest round of reforms is in the process since 2015. The participations of foreign and private investors enhance the diversification and performance of whole banking industry to some extent. However, under the special society system of China, big state- owned commercial banks (SOCBs) normally enjoy some natural advantages and the imbalance of regional development is a long-lived issue among the whole country. Although more and more researchers examined the performance of Chinese banks recent years, few of them studied the effect of regional features on banking performance. Firstly, this paper investigates both cost efficiency and profitability of 193 Chinese commercial banks during period of 2012 to 2016 and compare the performance of these banks in terms of ownership type and regional feature. The cost efficiency of banks is estimated via the Stochastic Frontier Analysis (SFA) technique with intermediation approach. Then, the two- step system Generalized Method of Moments (GMM) estimator is applied with a dynamic panel data model to estimate determinants of profitability in China’s banking sector. The empirical results suggest that Chinese SOCBs tend to be least efficient but most profitable while foreign banks have highest level of cost efficiency but lowest profitability in China. However, these situations may have some changes in 2016. In terms of regional effect, banks in relatively developed regions like East and Central economic regions remain a higher efficiency. However, banks in such more efficient regions like East region tend to be lower profitable may due to the more competitive environment. Lastly, the results of GMM model indicate that profitability of Chinese banks is influenced by both internal and external factors. Internal factors include some bank-specific determinants like liquidity level, credit risk, capital structure, cost efficiency and non-traditional activities while external factors are both industry-specific and macroeconomic determinants including market concentration, inflation, GDP growth and real estate index.